KURIKULUM PENDIDIKAN DALAM PERSPEKTIF IBNU TAIMIYAH DAN IBNU QAYYIM - Fauzah Nur 'Aini; As'adatun Niswah; Mulyanto Abdullah Khoir (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
This article examines the concept of educational curriculum from the perspectives of two great medieval Islamic scholars, namely Ibn Taymiyyah (661-728 H/1263-1328 CE) and Ibn Qayyim al-Jauziyyah (691-751 H/1292-1350 CE). Both figures possessed comprehensive and systematic views on Islamic educational curriculum rooted in the Qur’an and the Prophetic Sunnah. This study employs library research methodology with historical-philosophical and comparative approaches. The findings reveal that Ibn Taymiyyah viewed the educational curriculum as necessarily grounded in shar’i sciences as its primary foundation, placing knowledge of Allah (ma’rifatullah) at the apex of the knowledge hierarchy, with greater emphasis on the shar’i-fiqhi dimension at the institutional level. Meanwhile, Ibn Qayyim further developed his teacher’s thought by placing stronger emphasis on the psychological, spiritual, and integrative dimensions of learning, and offering an elaborate account of gradual child education according to developmental stages. A fundamental difference between the two lies in orientation: Ibn Taymiyyah focused more on curriculum reform at the social-institutional level, while Ibn Qayyim delved more deeply into the process of value internalization at the individual and family levels. Both scholars agreed that the primary objective of Islamic educational curriculum is the formation of individuals who are firmly grounded in tawhid, possess noble character, and are capable of fulfilling their trust as vicegerents on earth. The relevance of both scholars’ thought to contemporary Islamic education is highly significant, particularly within the framework of knowledge integration, character education, and holistic Islamic curriculum reform.